2013
DOI: 10.1186/1746-6148-9-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of engineered TiO2and ZnO nanoparticles on erythrocytes, platelet-rich plasma and giant unilamelar phospholipid vesicles

Abstract: BackgroundMassive industrial production of engineered nanoparticles poses questions about health risks to living beings. In order to understand the underlying mechanisms, we studied the effects of TiO2 and ZnO agglomerated engineered nanoparticles (EPs) on erythrocytes, platelet-rich plasma and on suspensions of giant unilamelar phospholipid vesicles.ResultsWashed erythrocytes, platelet-rich plasma and suspensions of giant unilamelar phospholipid vesicles were incubated with samples of EPs. These samples were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
33
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 53 publications
(50 reference statements)
4
33
0
1
Order By: Relevance
“…It seems evident that the binding of TiO 2 − with the membrane takes place through relatively weak contacts since NP did not immerse deeply in the membrane but floated on top of the bilayer surface, enabling diffusion of the membrane, with no adsorption to the membrane. This is in line with other study, where reported that a noticeable and statistically significant (p<0,001) influence on phospholipid vesicles were observed after incubation of ZnO (but not TiO 2 ) nanoparticles [33]. This is known that agglomerates larger than 0,2 μm were found attached to the membrane [34], whereas smaller aggregates and single particles could probably cross the membrane through pores or ion channels [35].…”
Section: Zno and Tio 2 Np's Interaction With Slbsupporting
confidence: 80%
See 1 more Smart Citation
“…It seems evident that the binding of TiO 2 − with the membrane takes place through relatively weak contacts since NP did not immerse deeply in the membrane but floated on top of the bilayer surface, enabling diffusion of the membrane, with no adsorption to the membrane. This is in line with other study, where reported that a noticeable and statistically significant (p<0,001) influence on phospholipid vesicles were observed after incubation of ZnO (but not TiO 2 ) nanoparticles [33]. This is known that agglomerates larger than 0,2 μm were found attached to the membrane [34], whereas smaller aggregates and single particles could probably cross the membrane through pores or ion channels [35].…”
Section: Zno and Tio 2 Np's Interaction With Slbsupporting
confidence: 80%
“…As this process could distort the membrane structure, characterization tools that enable us to study the structure (ordering) of the membrane also provide information about the influence of NPs on the membranes. ZnO and TiO 2 nanoparticles and their interaction with biological objects were investigated by several authors using different methods [6][7][8][9][10], however the mechanism of NP interaction with membrane is still an open question. Supercritical Angle Fluorescence Microscopy (SAF) is a technique that allows detection and characterisation of fluorescent species (proteins, biomolecules, pharmaceuticals, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…32,33 It is known that adsorption of NPs onto the surface of RBCs can change cell morphology and erythrocyte sedimentation rate, agglutination of RBCs, and hemolysis. 1,18,27,[34][35][36][37][38][39] An interesting question is whether mechanisms revealed by experimental studies of artificial membranes or computer simulations of interactions between NPs and artificial lipid membranes can also explain the interactions of NPs with biological membranes.…”
Section: Introductionmentioning
confidence: 99%
“…The NPs-induced RBC aggregation was lower with negatively charged NPs [11]. Similarly, Simundic et al reported on the induction of RBC aggregation by TiO 2 and ZnO NPs [12]. In addition, Smyth et al, have shown the induction of platelets aggregation by PS-NPs [13].…”
Section: Introductionmentioning
confidence: 91%
“…Numerous studies have examined NP-RBC interaction, focusing on the penetration of NPs into cells, [6,7] and the hemolytic potential of NPs [8][9][10], while only a few studies investigated the effect of NPs on cell-cell interaction [11,12]. In these studies, the effects of the size and surface charge of the hydroxyapatite NPs on the RBCs morphology and aggregation were investigated, showing that in protein-free medium, where no aggregation occurs, NPs induced RBC aggregation [11].…”
Section: Introductionmentioning
confidence: 99%